A Research Agenda: The Globalization of the Fresh Fruit and Vegetable System - H. Friedland , William; Goodman, David (The International Journal of Sociology of Agriculture and Food, 2021)
A workshop on the globalization of the fresh fruit and vegetable (FFV) system brought together numerous scholars from around the world at the University of Califoria - Santa Cruz. The FFV system has become truly global as evidenced by (1) the erosion of the seasonality of consumption via international sourcing and (2) the expansion of the product inventory. This has led to the development of non-traditional export agriculture in the Southern Hemisphere, which in turn has had many social, environmental and economic consequences, not all of which are found in all production locations. The distributional segment of the FFV system, where environmental issues dealing with energy intensivity and the sheer vollume of packaging are becoming ever more important, is dominated by a small number of sizable transnational corporations but the marketing sector seems, in effect, to drive the entire system. There is an increased demand for FFV because of rising levels of health and nutritional education, concern about consuming healthy food, worries about food safety, and the aging of populations in the advanced industrial nations. What emerged from the workshop is a growing recognition of the need to systematize the analysis of the FFV by creating a network of researchers and defining a research agenda which would include more topics, i.e. enviromnental and ecological conditions, and more disciplines, i.e. transportation geography/economics.